Surface‐enhanced Raman scattering of 4, 4'‐diaminostilbene: Dependence of spectral features and resonant enhancement on surface coverage. (24th January 2019) - Solovyeva, Elena V.
Abstract : A detailed profile deconvolution analysis was carried out for the concentration‐dependent surface‐enhanced Raman scattering spectra of 4, 4'‐diaminostilbene. The spectral signatures of the molecules located inside and outside hot spots regions were assigned. A resonance character of Raman enhancement accompanied by a charge transfer was revealed for the molecules adsorbed in the hot spots whereas it was absent on the uniformly amplifying surface.